Pelatihan Pembuatan Media Pembelajaran Interaktif Dengan Menggunakan Aplikasi Nearpod Bagi Guru Sekolah Dasar Di Gugus 8 Kecamatan Blimbing Kota Malang - Putra, Arda Purnama; Arafik, Muh; Muzaki, Ferril Ilham (STIE Malangkucecwara, 2023)
Blimbing District, Malang City consists of 12 sub-districts. Each subdistrict has an average of 2 elementary schools and 2 elementary schools with an average of 13 teachers in each elementary school and 1 elementary school principal. The average number of students in each elementary school is between 180-200 students. Almost all of the elementary school institutions in Blimbing District, Malang City, have the status of State Elementary Schools. The curriculum or learning used in elementary schools uses the 2013 curriculum. ICT facilities in elementary schools in Cluster 8, Blimbing District, Malang City are quite adequate. The education level of elementary school teachers in Cluster 8, Blimbing District, Malang City varies, many of them are PGSD Bachelor's graduates, some even have Master's degrees in Elementary Education. From the results of short interviews with several elementary school teachers in Cluster 8, Blimbing District, Malang City, it shows that teachers generally experience difficulties in creating teaching materials in the form of Interactive Learning Media. Through the community service program, it is hoped that elementary school teachers in Cluster 8, Blimbing District, Malang City will have (1) knowledge about digital teaching materials based on Interactive Learning Media, (2) skills in developing Interactive Learning Media teaching materials using the Nearpod application, (3) skilled abilities to practice (use) Interactive Learning Media teaching materials in online learning.